(untitled) (Journal of the Entomological Research Society, 2025)
In 2019 galls of black locust gall midge Obolodiplosis robiniae (Haldeman, 1847) (Diptera: Cecidomyiidae) were discovered in Türkiye on the black locust tree, Robinia pseudoacacia L. (Fabaceae) in Üçkardeş village (Kemalpaşa District, Artvin Province). The black locust gall midge is a new invasive species in Türkiye. Obolodiplosis robiniae was spread from Georgia.